Hygiene Hypothesis Indicators and Prevalence of Antinuclear Antibodies in US Adolescents - Meier, Helen C. S.; Sandler, Dale P.; Wilkerson, Jesse; Miller, Frederick W.; Dinse, Gregg E.; Parks, Christine G. (Frontiers in Immunology, 2022)
Autoimmunity prevalence, as measured by antinuclear antibodies (ANA), is increasing in U.S. adolescents. Improved hygiene and cleaner environments in childhood may reduce exposure to infections and other immune challenges, resulting in improper immune responses to later-life exposures. We examined associations of hygiene hypothesis indicators, including asthma, allergies, and antibodies to infectious agents, with ANA prevalence, measured by Hep-2 immunofluorescence, in adolescents (aged 12-19 years) over a 25-year time span in the National Health and Nutrition Examination Survey (NHANES) (N=2,709), adjusting for age, sex, race/ethnicity, body mass index, education and survey cycle, overall and within individual time periods, using logistic regression. Prevalence of ANA in adolescents increased from 5.0% in 1988-1991 to 12.8% in 2011-2012. ANA wereas positively associated with diagnosis of asthma in early childhood (OR: 2.07, CI: 1.09–3.99) and with the effect estimate for current hay fever was elevated but not statistically significant (OR: 1.55, CI: 0.85–2.84). Fewer than 2% of those with ANA in 1988-1991 had been diagnosed with asthma, compared with 18% in 1999-2000, and 27% in 2003-2004 and 2011-2012. ANA trended negatively with Helicobacter pylori antibodies (OR: 0.49, CI: 0.24–0.99). ANA may be useful as an additional indicator of inadequate immune education in adolescence, a critical period of growth and development.